Aportes de las controversias científicas y la resolución de problemas a la construcción del conocimiento del concepto enlace químico para docentes en formación - Ramírez C, Paula N.; Martínez, Karen; Peña, Luis (UNIVERSIDAD ANTONIO NARIÑO, 2012)
In this article are presented partial results of the use of the scientific controversy and resolution of problems in the design and implementation of a teaching unit about the concept of chemical bonding, as part of a research project conducted in the Undergraduate Curriculum Project in Chemistry Faculty of Science and Education of the University Francisco José de Caldas. In this paper we develop aspects such as: why are used Problem Solving and Scientific Controversy as teaching methodology for teachers in training, and the history of science as a central focus of both methodologies, we show results project phases and prospects of the remaining phases that are still developing